Persepsi Kekeliruan Guru Dalam Penerapan Kemampuan Pedagogik Di SMP Ma’arif 2 Ponorogo - Refina Dzurotul Mahmudah; Reza Pratama Putra; Tri Indah Setiyorini; Tria Mubarokah; Umi Hardiyanti Rokmana; Vio Regina Fairuz Zabad; Nurul Malika (Tamilis Synex: Multidimensional Collaboration, 2025)
The implementation of education involves many roles in it, one of which is the teacher as an active figure who guides and educates students directly. The role of teachers is very important to educate the nation's generation towards a better civilization. teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education, and secondary education. A teacher in addition to conveying knowledge, also forms good character and equips skills that are useful for students in the future. Teachers must have clear goals to achieve the mission of education so that it can be said that the teacher is competent in his field. But still in its application there are many mistakes that often arise which have an impact on the continuity of the learning process or perhaps the results of the learning process what are the causes of errors that often arise in the application of pedagogical competence. Errors in the application of pedagogical competence have several factors both internal and external, environmental factors, policy factors. The purpose of this study is to focus on teacher perceptions of common mistakes experienced in the application of pedagogical skills at Ma'arif 2 Ponorogo Junior High School, the strategic role of teachers in shaping students' learning experiences needs to be analyzed, besides that perceptions will provide descriptions of the extent to which teachers can know their shortcomings as well as become material for reflection to improve teacher quality.